Pioneering contribution of Professor Bruce Ames to early development in biochemical aspects of oxidatively generated damage to DNA - Cadet, Jean; Wagner, J. Richard (Frontiers in Molecular Biosciences, 2025)
The first part of the memorial review article is devoted to a retrospective of selected topics that were the subject of pioneering studies over the period 1985–2025 by Professor Bruce Ames. Major efforts were made to develop accurate and sensitive assays including HPLC coupled with electrochemical detection for monitoring the formation of 8-oxo-7,8-dihydroguanine in isolated cells and animal tissues. Special attention was provided to the minimization of artefactual oxidation of DNA that occurs during sample preparation. Complementary information on the biological relevance of 8-oxo-7,8-dihydroguanine and 5,6-dihydroxy-5,6-dihydrothymine was gained from the non-invasive measurement of the oxidized bases and nucleosides in various mammalian fluids. The second part of this review focuses on the current situation concerning the formation of oxidized bases in cellular DNA produced under various conditions of oxidative stress and enzymatic ten-eleven TET-oxidation of 5-methylcytosine. The analysis of DNA base modifications by LC-MS/MS is the gold standard for the quantitative monitoring of base oxidation products in both DNA and several body fluids; oxidizing conditions that may not be suitable for biological studies. Low levels of oxidatively-induced lesions in cells are difficult to assess by chromatographic and MS methods because of a significant increase in the yields of oxidized bases/nucleosides above the background level including a significant contribution of adventitious oxidation reactions that cannot be totally suppressed. In a complementary way, the application of modified versions of the comet assay and alkaline elution techniques that target general classes of DNA lesions provides a more global account of damage although it gives less structural information about DNA damage formed under chronic exposure to mild oxidizing conditions.